RATIONAL ANTIMICROBIAL THERAPY FOR GROUP A STREPTOCOCCAL TONSILLITIS IS THE BASIS FOR THE PRIMARYPREVENTION OF RHEUMATIC FEVER - Boris Sergeevich Belov; Boris Sergeyevich Belov (Современная ревматология, 2011)
Research Institute of Rheumatology, Russian Academy of Medical Sciences, Moscow Acute tonsillitis caused by group A β-hemolytic streptococcus (GABHS) remains an urgent problem. The paper provides evidence that suggests the resurgence of high-virulence GABHS infection and the increase in the frequency of its complications (acute rheumatic fever, toxic shock syndrome) and that there is a need for rational antibacterial therapy for this pathology. The drugs of choice for the treatment of the acute forms of GABHS tonsillitis are penicillins (amoxicillin, benzathine penicillin, phenoxymethylpenicillin) and first-generation cephalosporins (cefadroxil) and those for intolerance of β-lactam antibiotics are macrolides (spiramycin, azitromycin, roxithromycin, clarithromycin, josamycin, and midecamycin). Inhibitor-protected penicillins (amoxicillin-clavulanate) or second-generation cephalosporins (cefuroxime axetil) are administered in case of chronic recurrent GABHS tonsillitis when the probability of colonization of an infection focus by β-lactamase-producing microorganisms is rather high. The antibiotics lincosamines (lincomycin, clindamycin) are used as reserve drugs in therapy for acute and chronic GABHS tonsillitis.